PENGARUH Brand Ambassador dan Citra Merk terhadap Keputusan Pembelian Sepeda Motor Suzuki Type Nex - Gigih Wahyu Utomo; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is motivated by business competition in the current era of globalization more dynamic and complex, the existence of this competition not only raises opportunities but also poses a challenge. The challenges faced by competing companies are always trying to find the best way to seize and maintain market share. The company must be able to determine the right marketing strategy so that its business can survive and win the competition, so that the purpose of the company can be achieved. The first hypothesis that there is an influence between brand ambassador and customer purchase decisions has been proven. This is proven through research with the results of calculating the value of t arithmetic of 11.113 which is greater than t table 1.6772 which indicates that brand ambassador has a significant relationship to the purchase decision. So the one hypothesis that reads "there is influence between brand ambassador (X1) to purchase decision (Y)" accepted. The second hypothesis which states that there is an influence between the brand image of customer purchasing decisions has been proven. This is proven through research with the result of calculating the value of t arithmetic of 9.467 is greater than t table 1.6772 which indicates that brand image has a significant and significant influence on customer purchasing decisions. So the second hypothesis that reads "there is influence between brand image (X2) to customer purchasing decision (Y)" accepted. The results of this study in accordance with the results of research Hamid (2008) which states that the brand image has an effect on and significant to the purchase decision. T he third hypothesis states that there is a brand ambassador influence, and brand image of customer purchasing decisions is evident. This is proven through research with the result of calculating the value of F arithmetic equal to 83,430 which is bigger than f table 4.04 which indicate that brand ambassador, brand image, and trust to company have influence and signifikan to customer purchasing decision. So the second hypothesis that reads "there is influence between brand ambassador (X1), and brand image (X2) on customer purchasing decision (Y)" accepted